A robust hollow metal–organic framework with enhanced diffusion for size selective catalysis. Issue 45 (7th November 2022) - Wu, Chunhui; Zhao, Xiaowen; Wang, Dongxu; Si, Xiaomeng; Li, Tao
Abstract : A chemically robust single crystalline hollow MOF-801 containing Pt and Au nanoparticles was constructed by using UiO-66 as a sacrificial template for size selective catalysis with fast reaction kinetics under harsh chemical conditions. Abstract : Single crystalline (SC) hollow metal–organic frameworks (MOFs) are excellent host materials for molecular and nanoparticle catalysts. However, due to synthetic challenges, chemically robust SC hollow MOFs are rare. This work reports the construction of a defect-free and chemically stable SC hollow MOF, MOF-801(h), through templated growth from a unit cell mismatched core, UiO-66. Under the protection of excess MOF-801 ligand, fumaric acid, the MOF-801 shell was perfectly retained while the isoreticular UiO-66 core was selectively and completely etched away by formic acid. The combination of a large cavity, small aperture and short diffusion length allows the Pt nanoparticle encapsulated composite catalyst, Pt⊂MOF-801(h), to perform size selective hydrogenation of nitro compounds at an accelerated speed. Impressively, the catalyst can undergo concentrated HCl or boiling water treatment while maintaining its crystallinity, morphology, catalytic activity, and size selectivity. In addition, Au nanoparticles encapsulated catalyst, Au⊂MOF-801(h), was used for the size selective nucleophilic addition of HCl to terminal alkynes for the first time, which is a harsh reaction involving high concentrations of a strong acid.